The Influence of Organizational Culture, Organizational Structure, and Information Technology on Managerial Performance - Adrian, Muhamad Iqbal; Ikram, Syafrizal (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
Managerial performance is defined as one of the important factors in a company, because increasing managerial performance is expected to improve company performance. Managerial performance obtained by managers is also a factor that can be used to increase company effectiveness, managerial performance shows management's ability to carry out management functions which are business activities, which of course always involve decision making. This research aims to determine the influence of organizational culture, organizational structure and information technology on managerial performance. The type of data used in this research is primary data obtained from respondents' answers to a questionnaire submitted to winaya mukti university in bandung. the analytical method used is multiple linear regression analysis. data processing was carried out using spss version 22 for windows software with the spearman rank correlation analysis method. the research results show that organizational culture influences managerial performance, organizational structure influences managerial performance and information technology influences managerial performance.